2021
DOI: 10.1016/j.jbc.2021.100918
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillomarasmine A inhibits metallo-β-lactamases by selectively sequestering Zn2+

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…The sixth and final coordination site is occupied by a carboxylate oxygen (O7A) of an adjacently packed AMA-Ni 2+ complex, which we believe is a crystallization artifact. This hypothesis is based on our previous data, which showed that the binding of either Ni 2+ or Zn 2+ to AMA occurs with 1:1 stoichiometry in solution . Consequently, we suspect that the sixth coordination site of the AMA complex is likely occupied by solvent when dissolved under aqueous conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sixth and final coordination site is occupied by a carboxylate oxygen (O7A) of an adjacently packed AMA-Ni 2+ complex, which we believe is a crystallization artifact. This hypothesis is based on our previous data, which showed that the binding of either Ni 2+ or Zn 2+ to AMA occurs with 1:1 stoichiometry in solution . Consequently, we suspect that the sixth coordination site of the AMA complex is likely occupied by solvent when dissolved under aqueous conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, we identified a fungal Zn 2+ metallophore, aspergillomarasmine A (AMA) (Figure ), as an inhibitor of MBLs with excellent efficacy toward NDM and VIM-type enzymes. The mechanism of action of AMA involves selective Zn 2+ binding with picomolar affinity, which sequesters the metal in complex fluids . Consequently, AMA indirectly inhibits MBLs by outcompeting them for Zn 2+ even in the presence of common metals (Mg 2+ , Ca 2+ , and Fe 3+ ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since NDM-1 has been found widely in a total of 11 bacterial host families, new variants of NDM containing between 1 and 5 amino acid alterations have been continually generated, which indicates that amino acid substitution dominates the extension of MBL activity ( Wu et al, 2019 ). A233V substitution enabled NDM-6 to evolve higher enzyme fitness in the periplasm under the Zn(II) starvation condition than NDM-1 ( Bahr et al, 2018 ; Sychantha et al, 2021 ). To date, there are four additional bla NDM–6 -harbouring plasmids with complete sequences deposited in NCBI, which belonged to incompatibility groups IncHI2, IncX3, IncFII, and IncR from Leclercia adecarboxylata , K. pneumoniae and E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillomarasmine A (AMA) is a fungal natural product considered a rapid and potent MBL inhibitor that electively sequesters Zn 2+ (King et al, 2014 ; Sychantha et al, 2021 ). AMA itself is not antimicrobial but works in combination with β-lactam antibiotics or carbapenems against MBL producers, with an emphasis on VIM or NDM.…”
Section: Natural Productsmentioning
confidence: 99%